FOMC communication and interest rate sensitivity to news - Jenny Tang (Federal Reserve Bank of Boston, 2017)
In this paper, I examine whether communications by the Federal Open Market Committee (FOMC) play a role in determining the types of macroeconomic news that financial markets pay attention to. To do so, I construct novel measures of the intensity with which FOMC statements and meeting minutes discussed labor relative to other topics. I find that these labor topic intensity measures are related to the amount by which interest rates' response to labor-related news exceeds their response to all other news. This relationship is especially strong for interest rates of longer maturities and is also present for short-term interest rate expectations over various horizons.
Keywords: E43; E52; E58; G12; 330; Federal Reserve; FOMC; central bank communication; interest rates